The managerial prerogative on retrenchment in Malaysia - Hassan, Mumtaj; Hussain, Mohammad Azam; Md Desa, Md Rejab (2016)
Retrenchment is a situation wherein the contract of service of the employees are terminated due to surplus in workforce which occurs as a result of economic downturn, reorganization, reduction in production, mergers, takeover, and others. Although retrenchment is to be averted wherever possible, the industrial law recognizes the privilege of an employer to determine the appropriate economic size of its organization.This paper will attempt to discuss the legal aspect of retrenchment in Malaysia as provided in the statutes and guidelines. This paper also focuses on the managerial prerogative in termination of employees in case of redundancy, the recommendations in the Code of Industrial Harmony 1975, the legal effect of Last In First Out and the remedies for the redundant employees in Malaysia.